CDK4/6 Inhibition in Cancer: Beyond Cell Cycle Arrest. Issue 11 (November 2018) - Goel, Shom; DeCristo, Molly J.; McAllister, Sandra S.; Zhao, Jean J.
Abstract : Pharmacologic inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6) have recently entered the therapeutic armamentarium of clinical oncologists, and show promising activity in patients with breast and other cancers. Although their chief mechanism of action is inhibition of retinoblastoma (RB) protein phosphorylation and thus the induction of cell cycle arrest, CDK4/6 inhibitors alter cancer cell biology in other ways that can also be leveraged for therapeutic benefit. These include modulation of mitogenic kinase signaling, induction of a senescence-like phenotype, and enhancement of cancer cell immunogenicity. We describe here the less-appreciated effects of CDK4/6 inhibitors on cancer cells, and suggest ways by which they might be exploited to enhance the benefits of these agents for cancer patients. Highlights: Selective pharmacologic inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6) show immense promise as a treatment for a wide variety of cancers. The primary mechanism of CDK4/6 inhibitor activity is suppression of RB phosphorylation, enforcing G1 cell cycle arrest, and thus inhibiting proliferation. CDK4/6 inhibitors can also impact on other aspects of cancer cell behavior by inducing a senescence-like state, enhancing immunogenicity, and modulating kinase signaling. CDK4/6 inhibitors may also exert their activity through a direct effect on other cell types within tumors, including immune cells. Understanding the complex biological phenotypes induced by CDK4/6 inhibitors will ultimately allow the development of new therapeutic combinations to further benefit patients.